Line drawings : defining women through feminist practice - Heyes, Cressida J. (Cornell University Press, 2000)
At the heart of feminist theory lies the seemingly intractable issue of essentialism. Feminism has thus far failed to transcend critiques of essentialism and currently offers only two inadequate positions against it. One response reifies the category "women," representing the experience of oppression of privileged women as archetypal for feminism, and the other denies the category because it unjustly overgeneralizes, thus undercutting the possibility of a robust theory of gender oppression. To spur anti-essentialist methods and practice around such issues as sexual violence, feminist theory crucially needs a constructive and politically powerful strategy for defining women. Cressida J. Heyes deftly elucidates and then travels beyond the essentialism debates to rescue the efficacy of feminist theory for activism and research. She offers a genealogy of essentialism, specifically as it applies to the work of Carol Gilligan and Catharine MacKinnon, and employs a Wittgensteinian approach to feminism that understands similarities between women as family resemblances and political decisions about inclusion and exclusion as contextual and purposive. Line Drawings argues for an anti-essentialist method that enables generalizing feminist discourse but insists on paying close attention to the operations of power in constructing claims about women. This is a fresh and vitally important step past stymied debate on what is arguably the most pressing issue in cross-disciplinary feminist theory